Comparative study of zigzag and spiral tool path on sculpture surfaces. (2018) - Patel, Shivani S.; Patel, Divyangkumar D.; Saladi, Sekar
Abstract: Sculptured surfaces are widely used in aeronautical, mold and die industries. The tool path generation is an important step for the machining of free form surfaces. Many algorithms had been proposed for generating accurate and efficient tool path but most of them suffer from the certain drawback such as unequal spacing, variation in scallop height, etc. The accuracy, machining time, surface roughness etc., of the machined surface greatly depends on the selection of tool path such as zigzag or spiral tool path. In the present work, a comparative study of zigzag and spiral tool path on sculpture surface is carried out for batman logo using MASTERCAM TM X6 software.